(untitled) (REMUNOM, 2025)
Structural pathologies in civil engineering represent one of the main challenges in engineering, compromising the safety, durability, and functionality of buildings. These pathological manifestations can arise due to several factors, such as design flaws, execution errors, inadequate use of materials, lack of maintenance, and environmental actions. One solution to this problem is inspection. In view of this, the present study aimed to discuss the relevance of inspection as a preventive tool against structural pathologies, analyzing its benefits and impacts on the durability and safety of buildings. The methodology used was based on an integrative literature review, based on scientific articles, theses, and journals. Data collection was carried out through CAPES, Scielo, and Google Scholar databases, from 2019 to 2024. The results clearly show that efficient inspection reduces the occurrence of structural pathologies, as it ensures that technical standards and quality standards are correctly followed during all stages of construction. On the other hand, the lack of supervision or its inefficient execution increases the risk of structural failures, resulting in high corrective maintenance costs and putting user safety at risk.